GENDER EQUALITY IS A REQUIREMENT OF THE TIMES - Bazarbayeva Aynura Baxtiyarovna (International Journal on Orange Technologies, 2021)
The article will examine in detail the rights of women and men in the social sphere of society, the so-called gender equality. About the emergence, formation of equality, as well as what are the prospects for the development of gender equality at the present time.